THE EFFECT OF CHANGING THE RATE OF NITROGEN FERTILIZERS ON THE AMOUNT OF FAT IN SOYBEAN SEEDS (Intent Research Scientific Journal, 2023)
The article describes the effect of changing the level of oil content of nitrogen fertilizers in light gray soils of the Kashkadarya region, such as local and imported varieties Tumaris Man-60, Oydzhamol, Selecta-201, Amigo.